2018
DOI: 10.1007/s00425-018-3032-5
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of ethylene biosynthesis and perception during germination of dormant Avena fatua L. caryopses induced by KAR1 or GA3

Abstract: Main conclusion Germination of primary dormant wild oat caused by KAR 1 or GA 3 is associated with ACC accumulation and increased ethylene production shortly before radicle protrusion as a result of the non-transcriptional and transcriptional activation of ACS and ACO enzymes, respectively. Response to both compounds involves the modulation of ethylene sensitivity through ethylene receptor genes. Harvested Avena fatua caryopses are primary dormant and, therefore, germinated poorly at 20 °C. Karrikin 1 (KAR 1),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…The regulation of the germination process involves the hormonal balance between abscisic acid (ABA) and GA. While ABA promotes the establishment and maintenance of seed dormancy, GA acts in an antagonistic way, stimulating germination (Phengphachanh et al, 2012;Ruduoe et al, 2019). In fact, in the present study the highest germination rate was observed in the medium supplemented with the highest GA concentration.…”
Section: Discussionsupporting
confidence: 45%
“…The regulation of the germination process involves the hormonal balance between abscisic acid (ABA) and GA. While ABA promotes the establishment and maintenance of seed dormancy, GA acts in an antagonistic way, stimulating germination (Phengphachanh et al, 2012;Ruduoe et al, 2019). In fact, in the present study the highest germination rate was observed in the medium supplemented with the highest GA concentration.…”
Section: Discussionsupporting
confidence: 45%
“…1d). Fresh mature A. fatua diaspores exhibited physiological dormancy, which is controlled by hormones: ABA is involved in maintaining (Jones et al ., 2000) while GA and ethylene are involved in releasing this dormancy (Ruduś et al ., 2019). Treatment of dormant (D) A. fatua diaspores with GA or 4 months of dry storage (‘after‐ripening’) caused dormancy release (Figs 1e,f, S1) and upon imbibition, emergence of the coleorhiza was the first visible step during the germination process (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The coleorhiza is widespread beyond the grasses in other monocot species and in cycads but is absent in eudicots. Upon dormancy release, GA and ethylene induce the expression of CWRP genes including expansins, cellulases, mannanases and XTHs in the micropylar endosperm of eudicot seeds (Chen & Bradford, 2000; Toorop et al ., 2000; Chen et al ., 2002; Finch‐Savage & Leubner‐Metzger, 2006; Linkies et al ., 2009; Lee et al ., 2012; Martinez‐Andujar et al ., 2012; Graeber et al ., 2014) and the coleorhiza of Poaceae caryopses (Millar et al ., 2006; Barrero et al ., 2009; Gonzalez‐Calle et al ., 2015; Ruduś et al ., 2019) including A. fatua (this work). Interestingly, expansins are also expressed in the overlaying tissues during lateral root formation and the importance of the mechanical properties and of tissue interactions was proposed (Lucas et al ., 2013; Ramakrishna et al ., 2019).…”
Section: Discussionmentioning
confidence: 98%
“…In fire-following species, karrikins are used as germination cues, indicating the removal of competing plants. However, karrikins promote germination in a range of flowering plant species, which do not germinate after fire [2426] and KAI2 is required for a number of developmental traits in Arabidopsis not related to germination as well as for arbuscular mycorrhiza symbiosis in rice [19, 2730]. Because of these roles of KAI2, karrikins are thought to mimic the action of a yet unknown endogenous plant signalling molecule, which is currently denoted KAI2-ligand (KL) [3133].…”
Section: Introductionmentioning
confidence: 99%